1988
DOI: 10.1007/bf01745516
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte sodium content and transport in borderline and mild hypertension

Abstract: Sodium content and transport of red blood cells were examined in 98 male blood donors. Regarding their blood pressure they were classified into the following groups: (a) 57 normotensives, (RR less than 140/90 mm Hg); (b) 24 borderline hypertensives (140/90 less than or equal to RR less than 160/95 mm Hg); and (c) 17 hypertensives (RR greater than 160/100 mm Hg). Compared with the normotensives the borderline hypertensives have significantly reduced red cell sodium content. The ouabain-resistant net Na+ uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…3,4 In the present study, we found that hypertensives and their offspring had significantly lower RBC Ki compared to normotensives and that these levels were inversely related to DBP. Our data are consistent with previous studies showing a decreased RBC Ki in hypertensives and offspring of hypertensives [9][10][11] and a significant inverse relation- ship of RBC Ki and blood pressure. 12 Moreover, offspring of hypertensives had significantly lower RBC Ki levels and higher SBP than normotensive controls, suggesting that RBC Ki may decrease early in life in subjects susceptible to the development of future hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3,4 In the present study, we found that hypertensives and their offspring had significantly lower RBC Ki compared to normotensives and that these levels were inversely related to DBP. Our data are consistent with previous studies showing a decreased RBC Ki in hypertensives and offspring of hypertensives [9][10][11] and a significant inverse relation- ship of RBC Ki and blood pressure. 12 Moreover, offspring of hypertensives had significantly lower RBC Ki levels and higher SBP than normotensive controls, suggesting that RBC Ki may decrease early in life in subjects susceptible to the development of future hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…24,25 Although inhibition of Na + , K + -ATPase could explain the decreased RBC Ki levels, it would be expected to be accompanied by increased RBC Nai levels which we did not observe in our study. The fact that RBC Nai is not increased in hypertensives is supported by several studies 26,9,10 and opposed by others. 27,28 These discrepancies may be caused by differences in technique, 29 the type of population studied, inadequate sample size or the use of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 88%
“…co-workers who found reduced steady-state Na, and increased P,, of arteries removed from prehypertensive DOCA-salt-treated rats [57]. The same explanation was given by Engelhardt & Scholze [28] for their finding of reduced erythrocyte Na, in mild human hypertension.…”
Section: Discussionmentioning
confidence: 62%